Biochemical and histopathological profiling of Wistar rat treated with Brassica napus as a supplementary feed - Kazi Md. Mahmudul Hasan; Nasrin Tamanna; Md. Anwarul Haque (Food Science and Human Wellness)
Metabolic changes together with cardiovascular and hepatic factors are related to the development of diseases like myocardial lipidosis, heart disease, and profound toxicity. The aim of this animal study is to determine the effects of high erucic acid containing rapeseed oil (Brassica napus L.) varieties on liver, kidney and heart muscles in Wistar rats. Male Wistar rats were divided into three groups where each group containing four rats. Group A was considered as control diet group, while Group B rapeseed wild oil group and Group C rapeseed hybrid oil group were considered as experimental diet groups. The levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT),alkaline phosphatase(ALP), creatine kinase-MB (CK-MB) and creatinine of two experimental groups were significantly elevated while compared to the control groups (p < 0.05–0.001). Nevertheless, an increment in weight retardation (p < 0.05) was also observed in rapeseed hybrid oil treated groups. No significant weight retardation found in other two groups (p > 0.05). Noticeable tissue injury observed in this study is a sign of the relative toxicity of erucic acid containing rapeseed oil to mammalian species. The use of Brassica napus as a supplementary feed ingredient should be, therefore, thoroughly considered Keywords: Rapeseed oil, Rattus norvegicus, Serum enzymes, Erucic acid, Tissue profiling